Carbon fiber as well as preparation method and application thereof
Through the two-stage surface treatment method, weak layers on the carbon fiber surface are removed and oxygen-containing and nitrogen-containing functional groups are added, which solves the problems of inertia and low adsorption properties of the carbon fiber surface, and significantly improves the interface performance and overall performance of the composite material.
Patent Information
- Application Number
- CN202411539674.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
After high-temperature graphitization, the surface of carbon fibers exhibits chemical inertia and low adsorption, which makes it difficult for resin matrix to adhere effectively and affects the performance of composite materials.
Using a two-stage surface treatment method, firstly, the basic electrolyte with hydroxide root is used for the first stage surface treatment, to remove the weak layer on the surface of the fiber and increase the surface oxidative functional groups; then use a composite electrolyte of ammonium acetate and ammonium dihydrogen phosphate. Secondary surface treatment further enhances the oxygen-containing and nitrogen-containing functional groups on the surface of carbon fiber.
It significantly improves the interface performance between carbon fiber and resin matrix, enhances the interface bonding ability of composite materials, and improves the overall performance of composite materials.
Smart Images

Figure BDA0005112478790000161 
Figure BDA0005112478790000171
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon fiber surface modification, and in particular to a carbon fiber and a preparation method and application thereof. Background Art
[0002] Polyacrylonitrile-based high modulus carbon fiber is widely used in aerospace, national defense, military, and high-end sports equipment due to its high strength, high modulus, corrosion resistance, and low thermal expansion coefficient. However, after high-temperature graphitization treatment, the surface of this carbon fiber shows chemical inertness and low adsorption, which makes it difficult for the resin matrix to effectively adhere, thus affecting the performance of the composite material. In order to improve the surface structure of carbon fiber, researchers have explored a variety of surface treatment methods, such as electrochemical oxidation, gas / liquid phase oxidation, sizing, chemical grafting, and plasma treatment. Among them, electrochemical oxidation has become one of the most practical surface treatment technologies because of its mild treatment, controllable process, and online processing.
[0003] The selection of a suitable electrolyte solution during electrochemical oxidation treatment is an important factor affecting the treatment effect. The electrolytes used in the electrochemical oxidation treatment of carbon fiber surfaces can be divided into acids, bases and salts. Acid-base electrolytes are prone to corrode equipment and deteriorate the working environment. Alkali metal salt electrolytes are very likely to remain in the carbon fiber and become oxidation catalysts, reducing the ablation resistance of the carbon fiber. In addition, the factors that usually affect the interface bonding between carbon fiber and epoxy resin are the surface oxidation functional groups and roughness of the carbon fiber. However, the original graphite flakes on the surface of the carbon fiber are weakly bonded to the matrix, and the direct generation of oxygen-containing functional groups (such as hydroxyl and carboxyl) on the surface cannot significantly improve the interface performance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a method for preparing carbon fiber to at least solve one of the technical problems existing in the prior art. The carbon fiber preparation method adopts a two-stage surface treatment to remove the weak layer on the fiber surface and then increase the oxygen-containing functional groups and nitrogen-containing functional groups on the fiber surface, which can improve the interface performance of the carbon fiber.
[0006] A second object of the present invention is to provide a carbon fiber prepared by the carbon fiber preparation method.
[0007] The third object of the present invention is to provide an application of the carbon fiber in preparing a composite material. When preparing a composite material, the carbon fiber prepared by the carbon fiber preparation method is compounded with a resin matrix, which is beneficial to the interface bonding of the composite material.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a method for preparing carbon fiber, the method comprising the following steps:
[0010] Using polyacrylonitrile precursor as raw material, graphitized fiber is prepared, and then the graphitized fiber is subjected to electrochemical oxidation surface treatment and sizing in sequence to obtain carbon fiber;
[0011] The electrochemical oxidation surface treatment comprises: performing primary surface treatment and secondary surface treatment on the graphitized fiber in sequence, wherein the primary surface treatment uses an alkaline electrolyte containing hydroxide, and the secondary surface treatment uses a composite electrolyte of ammonium acetate and diammonium phosphate.
[0012] Further, the alkaline electrolyte having hydroxide includes at least one of sodium hydroxide and potassium hydroxide;
[0013] Preferably, the electrochemical oxidation surface treatment comprises anodizing surface treatment;
[0014] Preferably, the charge of the primary surface treatment is 200-400C / g, and the charge of the secondary surface treatment is 200-400C / g;
[0015] Preferably, the mass ratio of the ammonium acetate to the diammonium phosphate is 1:1;
[0016] Preferably, the time of the primary surface treatment is 10s to 30s, and the time of the secondary surface treatment is 10s to 30s;
[0017] Preferably, a graphite roller is provided at the outlet of the electrolyte tank for the secondary surface treatment, and the graphite roller is used to transport the graphitized fiber to the water washing tank;
[0018] Preferably, the inclination angle between the graphitized fiber and the graphite roller is 30° to 50°, and the bundle tension of the graphitized fiber is 50N to 80N.
[0019] Furthermore, the preparation process of the graphitized fiber includes: pre-oxidizing, carbonizing once, carbonizing twice and graphitizing the polyacrylonitrile precursor in sequence;
[0020] Preferably, the pre-oxidation, the primary carbonization, the secondary carbonization and the graphitization are all carried out in a gradient temperature increase manner;
[0021] Preferably, the pre-oxidation temperature is 200-300°C and the time is 1h to 2h;
[0022] Preferably, the pre-oxidation is set to 3-4 temperature zones, and the temperature difference between the temperature zones is 5-15°C;
[0023] Preferably, the primary carbonization temperature is 400-800°C and the time is 3min-5min;
[0024] Preferably, the primary carbonization equipment is provided with 6-8 temperature zones, and the temperature difference between the temperature zones is 40°C to 80°C;
[0025] Preferably, the temperature of the secondary carbonization is 1000-1600°C and the time is 2min-6min;
[0026] Preferably, the secondary carbonization equipment is provided with 5-6 temperature zones, and the temperature difference between the temperature zones is 50°C to 150°C;
[0027] Preferably, the graphitization temperature is 2000-2600°C and the time is 2min-6min;
[0028] Preferably, the graphitization equipment is provided with 4-5 temperature zones, and the temperature difference between the temperature zones is 100°C to 200°C.
[0029] Furthermore, before the sizing, the method further includes washing the graphitized fibers after the electrochemical oxidation surface treatment;
[0030] Preferably, the washing time is 100-150s;
[0031] Preferably, the water washing adopts a multi-stage water washing method;
[0032] Preferably, a water washing tank is used for water washing, and the water washing tank is provided with 4-6 sections;
[0033] Preferably, a plurality of baffles are provided inside the water washing tank, and the baffles are used to separate each section of the water washing;
[0034] Preferably, the heights of the plurality of baffles increase gradually along the running direction of the graphitized fibers after the electrochemical oxidation surface treatment in the water washing tank;
[0035] Preferably, the water flow in the water washing tank is opposite to the running direction of the graphitized fiber after the electrochemical oxidation surface treatment;
[0036] Preferably, a pipe for spraying is provided above the washing tank, and the pipe is provided with a plurality of holes.
[0037] Furthermore, before the sizing, the washed graphitized fibers are dried for the first time;
[0038] Preferably, the temperature of the first drying is 130-150°C.
[0039] Furthermore, the sizing agent used for sizing is an epoxy sizing agent.
[0040] Further, the sizing fibers are dried for a second time;
[0041] Preferably, the temperature of the second drying is 150°C to 250°C.
[0042] In a second aspect, the present invention provides a carbon fiber prepared by the carbon fiber preparation method.
[0043] In a third aspect, the present invention provides an application of carbon fiber in preparing a composite material.
[0044] In a fourth aspect, the present invention provides an application of the carbon fiber in preparing a composite material, wherein the composite material is prepared by the following steps:
[0045] The carbon fiber and the resin matrix are compounded to obtain the composite material.
[0046] Compared with the prior art, the present invention has the following beneficial effects:
[0047] The carbon fiber preparation method provided by the present invention adopts a two-stage surface treatment, wherein an alkaline electrolyte having hydroxide is used for the first-stage surface treatment, and a composite electrolyte of ammonium dihydrogen phosphate and ammonium acetate is used for the second-stage surface treatment. The alkaline electrolyte having hydroxide causes the surface of the graphitized fiber to be oxidized and etched, the surface grains are refined, the specific area is increased, and the roughness of the surface of the graphitized fiber after the surface treatment is increased. When the review material is subsequently prepared, the resin matrix can fully wrap and infiltrate the carbon fiber to form a physical concave-convex mosaic, which can play an anchoring role after the resin matrix is cured, and is beneficial to the interface bonding of the composite material; at the same time, the alkaline electrolyte having hydroxide can also effectively remove the weak layer on the surface of the graphitized fiber, and the OH - Ions can be inserted into the edge of the graphite sheet of the graphitized fiber, causing the carbon layer to peel off in the crystalline or amorphous area; after removing the graphite sheet on the surface of the graphitized fiber, the secondary surface treatment uses a composite electrolyte of ammonium dihydrogen phosphate and ammonium acetate. After the electrolysis of ammonium dihydrogen phosphate, acidic groups are generated. The acidic groups are located at the edge of the exposed graphite sheet, which can significantly improve the interface performance between the carbon fiber and the resin matrix. Although the treatment with ammonium dihydrogen phosphate can greatly improve the interlaminar shear strength of the carbon fiber, it will reduce its tensile properties. Therefore, an ammonium acetate electrolyte is used to quickly oxidize the surface of the carbon fiber to produce oxidation products. The composite electrolyte of ammonium dihydrogen phosphate and ammonium acetate has a better oxidation effect on the carbon fiber, which can increase the oxygen-containing functional groups and nitrogen-containing functional groups on the surface of the carbon fiber while maintaining the strength of the carbon fiber itself. DETAILED DESCRIPTION
[0048] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] A first aspect of the present invention provides a method for preparing carbon fiber, the method comprising the following steps:
[0051] Using polyacrylonitrile precursor as raw material, graphitized fiber is prepared, and then the graphitized fiber is subjected to electrochemical oxidation surface treatment and sizing in sequence to obtain carbon fiber;
[0052] The electrochemical oxidation surface treatment comprises: performing primary surface treatment and secondary surface treatment on the graphitized fiber in sequence, wherein the primary surface treatment uses an alkaline electrolyte containing hydroxide, and the secondary surface treatment uses a composite electrolyte of ammonium acetate and diammonium phosphate.
[0053] In the present invention, two-stage surface treatment is adopted, the first-stage surface treatment uses an alkaline electrolyte with hydroxide, and the second-stage surface treatment uses a composite electrolyte of ammonium acetate and ammonium dihydrogen phosphate. The alkaline electrolyte with hydroxide causes the surface of the graphitized fiber to be oxidized and etched, the surface grains are refined, the specific area is increased, and the roughness of the surface of the graphitized fiber after surface treatment is increased. When the composite material is subsequently prepared, the resin matrix can fully wrap and infiltrate the carbon fiber to form a physical concave-convex mosaic, which can play an anchoring role after the resin matrix is cured, which is beneficial to the interface bonding of the composite material; at the same time, the alkaline electrolyte with hydroxide can also effectively remove the weak layer on the surface of the graphitized fiber, OH -Ions can be inserted into the edge of the graphite sheet of the graphitized fiber, causing the carbon layer to peel off in the crystalline or amorphous area; after removing the graphite sheet on the surface of the graphitized fiber, the secondary surface treatment uses a composite electrolyte of ammonium acetate and diammonium phosphate. After the electrolysis of diammonium phosphate, acidic groups are generated. The acidic groups are located at the edge of the exposed graphite sheet, which can significantly improve the interface performance between the carbon fiber and the resin matrix. Although the treatment with diammonium phosphate can greatly improve the interlaminar shear strength of the carbon fiber, it will reduce its tensile properties. Therefore, an ammonium acetate electrolyte is used to quickly oxidize the surface of the carbon fiber to produce oxidation products. The composite electrolyte of ammonium acetate and diammonium phosphate has a better oxidation effect on the carbon fiber, which can increase the oxygen-containing functional groups and nitrogen-containing functional groups on the surface of the carbon fiber while maintaining the strength of the carbon fiber itself.
[0054] In some preferred embodiments, the alkaline electrolyte having hydroxide includes at least one of sodium hydroxide and potassium hydroxide;
[0055] The electrochemical oxidation surface treatment includes anodizing surface treatment;
[0056] Preferably, the charge of the primary surface treatment is 200-400C / g, for example, 200C / g, 250C / g, 300C / g, 350C / g, 400C / g, etc., and the charge of the secondary surface treatment is 200-400C / g, for example, 200C / g, 250C / g, 300C / g, 350C / g, 400C / g, etc.;
[0057] Preferably, the mass ratio of the ammonium acetate to the diammonium phosphate is 1:1;
[0058] Preferably, the time of the primary surface treatment is 10s to 30s, for example, 10s, 15s, 20s, 25s, 30s, etc.; the time of the secondary surface treatment is 10s to 30s, for example, 10s, 15s, 20s, 25s, 30s, etc.;
[0059] In the present invention, the specific amount of electricity and electrolyte time can be used to control the degree of oxidation on the carbon fiber surface, thereby avoiding excessive etching of the fiber surface due to excessive oxidation or insufficient surface treatment effect due to insufficient oxidation.
[0060] In the present invention, the electrolyte tank for primary surface treatment and the electrolyte tank for secondary surface treatment are arranged front and back according to the wire running direction of the wire bundle.
[0061] Preferably, a graphite roller is provided at the outlet of the electrolyte tank for the secondary surface treatment, and the graphite roller is used to transport the graphitized fiber to the washing tank, and a waste liquid collection tank with a length of 50 cm is provided below the graphite roller;
[0062] The inclination angle between the graphitized fiber and the graphite roller is 30° to 50°, preferably 40°, which helps the electrolyte residue carried by the fiber to drip into the waste liquid collection tank, which can reduce the amount of water used for rear-end washing and improve the washing effect. The tow tension of the graphitized fiber is 50N.
[0063] In some preferred embodiments, the polyacrylonitrile precursor is prepared by dry-jet wet spinning;
[0064] Preferably, the polyacrylonitrile precursor comprises AC65-12K.
[0065] In the present invention, AC65-12K prepared by dry-jet wet spinning is used as raw material, which has the advantage of high fiber performance and can meet the requirements of high-temperature and high-stretching carbonization process at the back end.
[0066] In some preferred embodiments, the preparation process of the graphitized fiber comprises: sequentially performing pre-oxidation, primary carbonization, secondary carbonization and graphitization on the polyacrylonitrile precursor;
[0067] Preferably, the pre-oxidation, the primary carbonization, the secondary carbonization and the graphitization are all carried out in a gradient temperature increase manner;
[0068] In the present invention, a gradient heating method is used to pre-oxidize, carbonize once (i.e., low-temperature carbonization), carbonize twice (i.e., high-temperature carbonization) and graphitize the polyacrylonitrile precursor to obtain graphitized fiber. The advantage of the gradient heating method is that it can ensure that the carbon fiber is evenly heated in various parts, avoiding local overheating or overcooling, thereby making the microstructure of the carbon fiber more uniform and reducing the occurrence of defects.
[0069] Preferably, the pre-oxidation temperature is 200-300°C, for example, 200°C, 250°C, 300°C, etc., and the time is 1h to 2h, for example, 1h, 1.5h, 2h, etc.;
[0070] Preferably, the pre-oxidation sets 3-4 temperature zones, for example, 3, 4, etc., and the temperature difference between the temperature zones is 5-15°C, for example, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, etc.;
[0071] In the present invention, one temperature zone of the pre-oxidation is an oxidation furnace. In the present invention, three oxidation furnaces for pre-oxidation are preferably provided. The temperature difference between the three oxidation furnaces is 5-15°C, which increases gradually. The temperature inside each oxidation furnace is constant, and the furnace temperature of each oxidation furnace must be uniform.
[0072] Preferably, the primary carbonization temperature is 400-800°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, etc., and the time is 3 min to 5 min, for example, 3 min, 4 min, 5 min, etc.;
[0073] Preferably, the primary carbonization equipment is provided with 6-8 temperature zones, for example, 6, 7, 8, etc., and the temperature difference between the temperature zones is 40°C to 80°C, for example, 40°C, 60°C, 80°C, etc.;
[0074] In the present invention, the primary carbonization (ie, low-temperature carbonization) adopts a low-temperature carbonization furnace, and a plurality of increasing temperature zones are arranged inside the low-temperature carbonization furnace.
[0075] Preferably, the temperature of the secondary carbonization is 1000-1600°C, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, etc., and the time is 2min-6min, for example, 2min, 4min, 6min, etc.;
[0076] Preferably, the secondary carbonization equipment is provided with 5-6 temperature zones, for example, 5, 6, etc., and the temperature difference between the temperature zones is 50°C to 150°C, for example, 50°C, 100°C, 150°C, etc.;
[0077] In the present invention, the secondary carbonization (ie, high-temperature carbonization) adopts a high-temperature carbonization furnace, and a plurality of increasing temperature zones are arranged inside the low-temperature carbonization furnace.
[0078] Preferably, the graphitization temperature is 2000-2600°C, for example, 2000°C, 2100°C, 2200°C, 2300°C, 2400°C, 2500°C, 2600°C, etc., and the time is 2min-6min, for example, 2min, 4min, 6min, etc.;
[0079] Preferably, the graphitization equipment is provided with 4-5 temperature zones, for example, 4, 5, etc., and the temperature difference between the temperature zones is 100°C to 200°C, for example, 100°C, 150°C, 200°C, etc.
[0080] In the present invention, graphitization is performed in a graphitization furnace, and a plurality of increasing temperature zones are arranged inside the graphitization furnace.
[0081] It should be noted that, in the present invention, an oxidation furnace for pre-oxidation is a temperature zone, and the temperature inside each oxidation furnace must be constant; in the low-temperature carbonization, high-temperature carbonization and graphitization steps, a single furnace is used, and several temperature zones with temperature differences are set in the furnace.
[0082] In some preferred embodiments, before the sizing, the graphitized fiber after the electrochemical oxidation surface treatment is further washed with water;
[0083] In the present invention, the graphitized fiber is surface treated by an anodic oxidation surface treatment method, impregnated with an electrolyte, and then washed with water. By washing with water, electrolyte residues from the primary and secondary surface treatments are prevented from entering the subsequent process, and the interface bonding ability of the carbon fiber when preparing the composite material can be further improved.
[0084] Preferably, the washing time is 100-150s, for example, it can be 100s, 110s, 120s, 130s, 140s, 150s, etc.;
[0085] Preferably, the water washing adopts a multi-stage water washing method;
[0086] Preferably, a water washing tank is used for water washing, and the water washing tank is provided with 4-6 sections, for example, 4 sections, 5 sections, 6 sections, etc., and a plurality of baffles are provided inside the water washing tank, and the baffles are used to separate each section of water washing, so as to facilitate better cleaning of surface electrolyte residues, wherein the heights of the plurality of baffles increase along the running direction of the graphitized fiber after the electrochemical oxidation surface treatment in the water washing tank, and the height difference of each baffle is 8mm to 10mm, and the water flow direction in the water washing tank is opposite to the running direction of the graphitized fiber after the electrochemical oxidation surface treatment;
[0087] Preferably, a pipe for spraying is provided above the washing tank, and the pipe is provided with a plurality of holes; wherein the diameter of the holes is preferably 5 mm;
[0088] Preferably, the pipeline comprises a 304 stainless steel pipe, and the number of the pipeline is 2-4, for example, 2, 3, 4, etc.;
[0089] Preferably, the end water washing conductivity of the water washing tank is at most 50 us / cm, preferably at most 20 us / cm.
[0090] In some preferred embodiments, after the washing and before the sizing, the washed fiber is dried for the first time;
[0091] Preferably, the temperature of the first drying is 130-150°C, for example, 130°C, 135°C, 140°C, 145°C, 150°C, etc.
[0092] In some preferred embodiments, the sizing agent used for sizing is an epoxy sizing agent.
[0093] In some preferred embodiments, the sizing fibers are dried a second time;
[0094] Preferably, the temperature of the second drying is 150°C to 250°C, for example, 150°C, 200°C, 150°C, etc.
[0095] Furthermore, the carbon fiber preparation method comprises the following steps:
[0096] (1) Pre-oxidation, low-temperature carbonization, high-temperature carbonization and graphitization are performed on dry-jet wet-spun polyacrylonitrile precursor by a gradient heating method to obtain graphitized fibers;
[0097] (2) The graphitized fiber is treated with an anodic oxidation surface treatment method, impregnated with an electrolyte, and then washed with water;
[0098] (3) The washed fibers are dried by a drying roller to remove surface moisture, and then sizing and drying are performed to obtain high-strength and high-modulus carbon fibers.
[0099] A second aspect of the present invention provides a carbon fiber prepared by the carbon fiber preparation method.
[0100] In the present invention, the carbon fiber preparation method can be used to prepare a high-strength and high-modulus carbon fiber with high interface performance.
[0101] A third aspect of the present invention provides an application of the carbon fiber in preparing a composite material, wherein the composite material is prepared by the following steps:
[0102] The carbon fiber and the resin matrix are compounded to obtain the composite material.
[0103] Preferably, the resin matrix includes epoxy resin, and the high-strength and high-modulus carbon fiber is compounded with the epoxy resin to obtain a composite material with significantly improved interface properties.
[0104] When preparing a composite material, the carbon fiber prepared by the carbon fiber preparation method is compounded with a resin matrix, which is beneficial to the interface bonding of the composite material.
[0105] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0106] Example 1
[0107] This embodiment provides a method for preparing carbon fiber, comprising the following steps:
[0108] Step 1: pre-oxidizing, low-temperature carbonizing, high-temperature carbonizing and graphitizing the dry-jet wet-spun AC65-12K precursor by a gradient heating method to obtain graphitized fibers;
[0109] The pre-oxidation process includes: the dry-jet wet-spinning AC65-12K precursor is sequentially pre-oxidized in three oxidation furnaces, the temperatures of the three oxidation furnaces are 230°C, 240°C, and 250°C, the treatment time of each oxidation furnace is the same, and the total pre-oxidation time is 1.5h;
[0110] Among them, low-temperature carbonization includes: the pre-oxidized tow passes through 7 temperature zones in the low-temperature carbonization furnace in turn for low-temperature carbonization, the temperatures of the 7 temperature zones are 400°C, 460°C, 520°C, 580°C, 640°C, 700°C, and 760°C, the treatment time of each temperature zone is the same, and the total residence time of low-temperature carbonization is 4 minutes;
[0111] The high-temperature carbonization includes: the filament bundle after low-temperature carbonization is sequentially passed through 5 temperature zones in the high-temperature carbonization furnace for high-temperature carbonization, the temperatures of the 5 temperature zones are 1000°C, 1100°C, 1200°C, 1300°C, and 1400°C, the processing time of each temperature zone is the same, and the total residence time of high-temperature carbonization is 4 minutes;
[0112] Among them, graphitization includes: the filament bundle after high-temperature carbonization is sequentially passed through 4 temperature zones of the graphitization furnace for graphitization treatment, the temperatures of the 4 temperature zones are 2000°C, 2150°C, 2300°C, and 2450°C respectively, the treatment time of each temperature zone is the same, and the graphitization time is 4 minutes.
[0113] Step 2: The prepared graphitized fiber is subjected to an anodic oxidation surface treatment method, and is sequentially impregnated with the electrolyte in the two-stage surface treatment, and then washed with water;
[0114] The electrolyte for the primary surface treatment is sodium hydroxide, the surface treatment charge is 250C / g, and the treatment time is 20s; the electrolyte for the primary surface treatment is a composite electrolyte of ammonium acetate and diammonium phosphate, the mass ratio of ammonium acetate to diammonium phosphate is 1:1, the surface treatment charge is 350C / g, and the treatment time is 20s;
[0115] Among them, the electrolyte outlet of the secondary surface treatment passes through a graphite roller, the inclination angle between the fiber and the graphite roller is 40°, there is a 50cm long waste liquid collection tank under the graphite roller, and the tow tension is 75N;
[0116] Among them, the fibers after two-stage electrolysis are washed with water for 125s. The washing tank is a multi-stage washing tank with 5 sections. Each section is composed of baffles from low to high along the running direction of the tow. The height of each baffle differs by 10mm step by step, and the water flows from the back section to the front section. Four 304 stainless steel pipes are opened above the washing tank for spraying, and the stainless steel pipes have several pores with a diameter of 5mm.
[0117] Step 3: The washed fibers are dried by a 145°C drying roller to remove surface moisture, sizing with an epoxy sizing agent and then dried at a drying temperature of 200°C to obtain high-strength and high-modulus carbon fibers with a high interface.
[0118] Example 2
[0119] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0120] In step 2, the charge for the secondary surface treatment is 400C / g;
[0121] The remaining steps are consistent with Example 1.
[0122] Example 3
[0123] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0124] In step 2, the charge for the primary surface treatment is 400C / g;
[0125] The remaining steps are consistent with Example 1.
[0126] Example 4
[0127] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0128] In step 2, the charge for the secondary surface treatment is 200C / g;
[0129] The remaining steps are consistent with Example 1.
[0130] Example 5
[0131] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0132] In step 2, the charge for the primary surface treatment is 200C / g, and the charge for the secondary surface treatment is 300C / g;
[0133] The remaining steps are consistent with Example 1.
[0134] Example 6
[0135] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 2 in that:
[0136] In step 2, the charge for primary surface treatment is 350C / g;
[0137] The remaining steps are consistent with Example 2.
[0138] Example 7
[0139] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0140] In step 2, two 304 stainless steel pipes are opened above the water washing tank for spraying;
[0141] The remaining steps are consistent with Example 1.
[0142] Example 8
[0143] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0144] In step 2, no 304 stainless steel pipe spraying was used above the washing tank.
[0145] Example 9
[0146] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0147] In step 2, the electrolyte for the primary surface treatment is KOH;
[0148] The remaining steps are consistent with Example 1.
[0149] Example 10
[0150] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0151] In step 1, pre-oxidation includes: the dry-jet wet-spinning AC65-12K precursor is sequentially passed through 4 oxidation furnaces for pre-oxidation, and the temperatures are 200°C, 215°C, 230°C, and 245°C, respectively. The treatment in each temperature zone is the same, and the total pre-oxidation time is 1 hour;
[0152] Among them, low-temperature carbonization includes: the pre-oxidized tow enters the low-temperature carbonization furnace and passes through 6 temperature zones in sequence. The temperatures of the 6 temperature zones are 400°C, 480°C, 560°C, 640°C, 720°C, and 800°C respectively. The processing time of each temperature zone is the same, and the total residence time of low-temperature carbonization is 3 minutes;
[0153] Among them, high-temperature carbonization includes: the filament bundle after low-temperature carbonization enters the high-temperature carbonization furnace and passes through 6 temperature zones in sequence. The temperatures of the 6 temperature zones are 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, and 1250°C respectively. The processing time of each temperature zone is the same, and the total residence time of high-temperature carbonization is 6 minutes;
[0154] The graphitization process includes: the filament bundle after high-temperature carbonization enters the graphitization furnace and passes through five temperature zones in sequence. The temperatures of the five temperature zones are 2000°C, 2100°C, 2200°C, 2300°C, and 2400°C, respectively. The treatment time of each zone is the same, and the total graphitization time is 6 minutes.
[0155] In step 2, the tilt angle is 30°;
[0156] In step 3, the washed fiber is dried by a drying roller at 130°C, and the drying temperature after sizing is 250°C;
[0157] The remaining steps are consistent with Example 1.
[0158] Embodiment 11
[0159] This embodiment provides a method for preparing carbon fiber, which is different from Embodiment 1 in that:
[0160] In step 1, pre-oxidation includes: the dry-jet wet-spinning AC65-12K precursor is sequentially passed through 4 oxidation furnaces for pre-oxidation, and the temperatures are 285°C, 290°C, 295°C, and 300°C, respectively. The treatment time in each temperature zone is the same, and the total pre-oxidation time is 2 hours;
[0161] Among them, low-temperature carbonization includes: the pre-oxidized tow enters the low-temperature carbonization furnace and passes through 8 temperature zones in sequence. The temperatures of the 8 temperature zones are 400°C, 440°C, 480°C, 520°C, 560°C, 600°C, 640°C, and 680°C, respectively. The processing time of each temperature zone is the same, and the total residence time of low-temperature carbonization is 5 minutes;
[0162] Among them, high-temperature carbonization includes: the filament bundle after low-temperature carbonization enters the high-temperature carbonization furnace and passes through 6 temperature zones in sequence. The temperatures of the 6 temperature zones are 1000°C, 1150°C, 1300°C, 1450°C, 1500°C, and 1600°C respectively. The processing time of each temperature zone is the same, and the total residence time of high-temperature carbonization is 2 minutes;
[0163] The graphitization process includes: the filament bundle after high-temperature carbonization enters the graphitization furnace and passes through five temperature zones in sequence. The temperatures of the five temperature zones are 2000°C, 2200°C, 2300°C, 2500°C, and 2600°C, respectively. The treatment time of each temperature zone is the same, and the total graphitization time is 2 minutes.
[0164] In step 2, the tilt angle is 50°;
[0165] In step 3, the washed fiber is dried by a 150° C. drying roller, and the drying temperature after sizing is 150° C.;
[0166] The remaining steps are consistent with Example 1.
[0167] Examples 12-22
[0168] Examples 12-22 provide an application of carbon fiber prepared by a carbon fiber preparation method in preparing composite materials. The carbon fibers prepared in Examples 1-11 are respectively compounded with epoxy resin Huibo WP-S5001 to obtain composite materials with significantly improved interface properties of Examples 12-22.
[0169] Comparative Example 1
[0170] This comparative example provides a method for preparing carbon fiber, which is different from Example 1 in that:
[0171] The electrolyte for primary and secondary surface treatments was sodium hydroxide, and the surface treatment charges were 250C / g and 350C / g, respectively;
[0172] The remaining steps are consistent with Example 1.
[0173] Comparative Example 2
[0174] This comparative example provides a method for preparing carbon fiber, which is different from Example 1 in that:
[0175] The electrolyte for primary and secondary surface treatments was sodium hydroxide, and the surface treatment charge was 250C / g;
[0176] The remaining steps are consistent with Example 1.
[0177] Comparative Example 3
[0178] This comparative example provides a method for preparing carbon fiber, which is different from Example 1 in that:
[0179] In step 2, the electrolyte for the secondary surface treatment is ammonium acetate;
[0180] The remaining steps are consistent with Example 1.
[0181] Comparative Example 4
[0182] This comparative example provides a method for preparing carbon fiber, which is different from Example 1 in that:
[0183] In step 2, the electrolyte for the secondary surface treatment is ammonium dihydrogen phosphate;
[0184] The remaining steps are consistent with Example 1.
[0185] Comparative Examples 5-8
[0186] Comparative Examples 5-8 provide an application of carbon fibers prepared by a carbon fiber preparation method in preparing composite materials. The carbon fibers prepared in Comparative Examples 1-4 are respectively compounded with epoxy resin Huibo WP-S5001 to obtain composite materials with significantly improved interface properties of Comparative Examples 5-8.
[0187] Test Case
[0188] Test samples and test methods:
[0189] The carbon fibers prepared in Examples 1-11 and Comparative Examples 1-4 were respectively used as Sample 1, and the tensile strength and tensile elastic modulus were tested according to GB / T3362, and O / C and N / C were measured using an X-ray photoelectron spectrometer. The test results are shown in Table 2.
[0190] The composite materials prepared in Examples 12-22 and Comparative Examples 5-8 were respectively used as Sample 2, and interlaminar shear strength test was performed according to ASTM D2344. The test results are shown in Table 2.
[0191] Table 1
[0192]
[0193]
[0194] It can be seen from the data in Table 1 that when Example 1 and Example 12 use a primary sodium hydroxide charge of 250C / g and a compound secondary charge of 350C / g, the tensile strength of the carbon fiber body reaches 4530MPa, the modulus reaches 488GPa, the layer shear strength reaches 86MPa, the O / C reaches 0.36, and the N / C reaches 0.21. Compared with Comparative Example 1 and Comparative Example 5, when both levels use sodium hydroxide electrolyte, the fiber strength is increased by 14.6%, the layer shear is increased by 32.3%, the oxygen-containing functional groups are increased by 44%, and the nitrogen-containing functional groups are increased by 9.5%, thereby greatly improving the fiber interface performance. It can be seen from the data of the embodiments that appropriate oxidation can improve the interfacial bonding strength between carbon fiber and epoxy resin, while excessive oxidation will reduce the interfacial bonding strength (i.e., interlaminar shear strength).
[0195] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing carbon fiber, characterized in that: The carbon fiber preparation method comprises the following steps: Using polyacrylonitrile precursor as raw material, graphitized fiber is prepared, and then the graphitized fiber is subjected to electrochemical oxidation surface treatment and sizing in sequence to obtain carbon fiber; The electrochemical oxidation surface treatment comprises: performing primary surface treatment and secondary surface treatment on the graphitized fiber in sequence, wherein the primary surface treatment uses an alkaline electrolyte containing hydroxide, and the secondary surface treatment uses a composite electrolyte of ammonium acetate and diammonium phosphate.
2. The method for preparing carbon fiber according to claim 1, characterized in that: The alkaline electrolyte having hydroxide includes at least one of sodium hydroxide and potassium hydroxide; Preferably, the electrochemical oxidation surface treatment comprises anodizing surface treatment; Preferably, the charge of the primary surface treatment is 200-400C / g, and the charge of the secondary surface treatment is 200-400C / g; Preferably, the mass ratio of the ammonium acetate to the diammonium phosphate is 1:1; Preferably, the time of the primary surface treatment is 10s to 30s, and the time of the secondary surface treatment is 10s to 30s; Preferably, a graphite roller is provided at the outlet of the electrolyte tank for the secondary surface treatment, and the graphite roller is used to transport the graphitized fiber to the washing tank; Preferably, the inclination angle between the graphitized fiber and the graphite roller is 30° to 50°, and the bundle tension of the graphitized fiber is 50N to 80N.
3. The method for preparing carbon fiber according to claim 1, characterized in that: The preparation process of the graphitized fiber includes: pre-oxidation, primary carbonization, secondary carbonization and graphitization of the polyacrylonitrile precursor in sequence; Preferably, the pre-oxidation, the primary carbonization, the secondary carbonization and the graphitization are all carried out in a gradient temperature increase manner; Preferably, the pre-oxidation temperature is 200-300°C and the time is 1h to 2h; Preferably, the pre-oxidation is set to 3-4 temperature zones, and the temperature difference between the temperature zones is 5-15°C; Preferably, the primary carbonization temperature is 400-800°C and the time is 3min-5min; Preferably, the primary carbonization equipment is provided with 6-8 temperature zones, and the temperature difference between the temperature zones is 40°C to 80°C; Preferably, the temperature of the secondary carbonization is 1000-1600°C and the time is 2min-6min; Preferably, the secondary carbonization equipment is provided with 5-6 temperature zones, and the temperature difference between the temperature zones is 50°C to 150°C; Preferably, the graphitization temperature is 2000-2600°C and the time is 2min-6min; Preferably, the graphitization equipment is provided with 4-5 temperature zones, and the temperature difference between the temperature zones is 100°C to 200°C.
4. The method for preparing carbon fiber according to claim 1, characterized in that: Before the sizing, the method further includes washing the graphitized fibers after the electrochemical oxidation surface treatment; Preferably, the washing time is 100-150s; Preferably, the water washing adopts a multi-stage water washing method; Preferably, a water washing tank is used for water washing, and the water washing tank is provided with 4-6 sections; Preferably, a plurality of baffles are provided inside the water washing tank, and the baffles are used to separate each section of the water washing; Preferably, the heights of the plurality of baffles increase gradually along the running direction of the graphitized fibers after the electrochemical oxidation surface treatment in the water washing tank; Preferably, the water flow in the water washing tank is opposite to the running direction of the graphitized fiber after the electrochemical oxidation surface treatment; Preferably, a pipe for spraying is provided above the washing tank, and the pipe is provided with a plurality of holes.
5. The method for preparing carbon fiber according to claim 4, characterized in that: Before the sizing, the washed graphitized fibers are dried for the first time; Preferably, the temperature of the first drying is 130-150°C.
6. The method for preparing carbon fiber according to claim 1, characterized in that: The sizing agent used for the sizing is an epoxy type sizing agent.
7. The method for preparing carbon fiber according to claim 1, characterized in that: Dry the sizing fibers for a second time; Preferably, the temperature of the second drying is 150°C to 250°C.
8. Carbon fiber prepared by the carbon fiber preparation method according to any one of claims 1 to 7.
9. Use of the carbon fiber as claimed in claim 8 in preparing composite materials.
10. The use of the carbon fiber in preparing a composite material according to claim 9, characterized in that: The composite material is prepared by the following steps: The carbon fiber and the resin matrix are compounded to obtain the composite material.
Citation Information
Patent Citations
Preparation method of high-modulus graphite fibers
CN104047070A
Polyacrylonitrile-based graphite fiber and preparation method thereof
CN110067044A
Preparation method of high-strength high-modulus wear-resisting polyacrylonitrile-based carbon fiber through dry spraying and wet spinning
CN110409018A
Surface treatment method of dry-jet wet-spinning high-modulus carbon fibers
CN114086386A
Method for surface treatment of carbon fiber
JP1995189113A
Cited By
Carbon fibers, and preparation method therefor and use thereof
WO2026091416A1